1990
DOI: 10.1159/000129090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Portal Hypertension by Portal Venous Stenosis on Systemic Hemodynamics in Dogs

Abstract: Effects of acute portal hypertension on systemic hemodynamics after hepatectomy were evaluated by portal venous stenosis (PVS) model in dogs. In protocol 1, portal hypertension of about twice portal venous pressure (PVP) decreased cardiac output (CO) and left atrial pressure (LAP) by 24.5% (p < 0.01) and 1.0 mm Hg (p < 0.01), respectively. In protocol 2, stepwise PVS demonstrated that CO change (%) and LAP change (mm Hg) were inversely proportional to PVP change (r = -0.937 and -0.883, respectively). The ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…11,12 It is well known that clamping of the inferior vena cava vein and portal vein causes an significant elevation of venous pressures (Table 3) and damages both the gastrointestinal mucosa (Fig. 1) and the abdominal organs because of the release of chinines, cytokines (tumor necrosis factor, interleukin), and vasoactive mediators, [13][14][15] which may also interfere with the cardiocirculatory function, 16,17 but there is actually evidence that a correct anaesthesiologic protocol, especially in regard to analgesia and fluid management, improves the outcome of animals after clamping and activation of the porto-intracaval shunt.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 It is well known that clamping of the inferior vena cava vein and portal vein causes an significant elevation of venous pressures (Table 3) and damages both the gastrointestinal mucosa (Fig. 1) and the abdominal organs because of the release of chinines, cytokines (tumor necrosis factor, interleukin), and vasoactive mediators, [13][14][15] which may also interfere with the cardiocirculatory function, 16,17 but there is actually evidence that a correct anaesthesiologic protocol, especially in regard to analgesia and fluid management, improves the outcome of animals after clamping and activation of the porto-intracaval shunt.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moriura et al experimentally analyzed hemodynamic changes after artificial portal vein stenosis, and showed that a sudden increase in portal vein pressure of about twice normal causes a statistically significant decrease of approximately 1 mmHg in right arterial pressure, as well as a 24% decrease in cardiac output. 18 If we consider that the liver receives approximately 25% of cardiac output, we can assume that portal vein clamping is associated with this indirect reduction in arterial blood flow of about 25%. 19 Thus, acute portal hypertension could initially be associated with liver arterial hypoperfusion.…”
Section: à13mentioning
confidence: 99%
“…20 When the caval vein is also clamped, the reduction in venous inflow to the heart is higher (75%); cardiac output is thus greatly reduced, and rapidly leads to the death of the animal. 18 Because of this, prolonged portal venous stenosis results in high mortality. However, Monchik et al showed that ischemia time of up to 1 h does not adversely affect the microscopic appearance of the bowel.…”
Section: à13mentioning
confidence: 99%
“…Acute portal hypertension may also determine systemic hemodynamic disturbances such as decreased venous return and systemic arterial pressure -the situation can induce splanchnic hypoperfusion and resultant change in mucosal histology -and motility. In addition, Moriura et al 11 showed a reduction in cardiac output and maintenance of left atrial pressure, suggesting no decrease in venous return. Thus, the mechanisms of hemodynamic changes after partial occlusion of the portal vein remain controversial.…”
mentioning
confidence: 99%